Inclusion [videorecording] learning together. #6 & 7 Functioning in the regular education classroom and classes, part I & II - Brown, Lou; Eisenhauer, Ardith; Orlowski, Gregg; University of Wisconsin-Madison. (Lincoln, N.E. Distributed by Destination Education, Lincoln, 1998)
"Lou Brown on classroom strategies for meeting the needs of students with significant disabilities."
The objective of the videos is to stimulate conversations between teachers, administrators, parents and teacher educators about practices of educating students with disabilities. In these segments Lou Brown talks on classroom strategies for meeting the needs of students with significant disabilities.
"DVD-R."
Keywords: Inclusive education; Special education; Mainstreaming in education; Students with disabilities